Pembelajaran Kitab Kuning dalam Meningkatkan Pemahaman Agama Islam Siswa di Mudarrisul Abrar Al-Aziziyah - Anggoro, Sasmitro; Miswar, Miswar (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to explore the role of learning the yellow book (Kitab Kuning) in improving students' understanding of Islam at Mudarrisul Abrar Al-Aziziyah. This study employed qualitative methods, collecting data through participant observation, interviews, and documentation. Data analysis was conducted through three stages: data reduction, data presentation, and conclusion drawing, to obtain a comprehensive picture of the process of learning the yellow book and its influence on improving students' religious understanding. The results indicate that learning the yellow book plays a significant role in improving the quality of students' knowledge and understanding of Islam. Through a textual interpretation approach, explanations of the socio-religious context, and interpretive discussions with teachers, students are able to understand Islamic teachings more deeply and apply them to their daily lives. Learning the yellow book also trains students' critical and analytical thinking skills regarding classical and contemporary Islamic values. The implications of this study indicate that learning the yellow book is not only relevant as a traditional religious study but can also be used as a contextual learning model in Islamic educational institutions to strengthen students' religious understanding and practice. Therefore, yellow book learning activities need to be continuously developed with more interactive and integrative methods to contribute to increasing Islamic literacy among students.